Renewable energy cost-benefit analysis under Malaysian feed-in-tariff - Abdullah, A. S. (2012)
Penetration of renewable energy sources in Europe have increased significantly for the past 10 years, especially in Germany. One important factor contributing to this improvement is the introduction of Feed-in Tariff (FiT). Follow in the footsteps of Europe, Malaysia has also introduced the FiT in 2011 to attract more investment in power generation from renewable energy (RE). This paper will investigate the cost-benefit analysis of installing Building-Integrated Photo-Voltaic (BIPV) system under the current FiT design in Malaysia. The analysis is performed by using HOMER software.